2015
DOI: 10.1111/rda.12591
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Rates to Fixed Embryo Transfer of Vitrified IVP Bos indicus, Bos taurus or Bos indicus × Bos taurus Embryos

Abstract: The pregnancy rates obtained after the transfer of cryopreserved in vitro-produced (IVP) embryos are usually low and/or inconsistent. The objective of this study was to evaluate the pregnancy rates of Holstein, Gyr and Holstein × Gyr cattle after the transfer of vitrified IVP embryos produced with X-sorted sperm. Seventy-two Gyr and 703 Holstein females were subjected to ovum pickup (OPU) sessions, followed by in vitro embryo production using semen from sires of the same breeds. Embryos (1636 Holstein, 241 Gyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
0
8
0
4
Order By: Relevance
“…Vitrification is a practical cryopreservation technique for somatic cells, gametes and preimplantation embryos and has important advantages over conventional freezing, such as its straightforward protocol and competitive costs while not requiring expensive equipment (vaJta et al, 1996;chian et al, 2004;marinho et al, 2015;Leme et al, 2016). Furthermore, vitrification has been extensively studied in an attempt to efficiently cryopreserve IVP embryos (araúJo-Lemos et al, 2014 since these embryos have shown reduced cryotolerance compared to their in vivo counterparts (tominaga, 2004;mucci et al, 2006;Leme et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitrification is a practical cryopreservation technique for somatic cells, gametes and preimplantation embryos and has important advantages over conventional freezing, such as its straightforward protocol and competitive costs while not requiring expensive equipment (vaJta et al, 1996;chian et al, 2004;marinho et al, 2015;Leme et al, 2016). Furthermore, vitrification has been extensively studied in an attempt to efficiently cryopreserve IVP embryos (araúJo-Lemos et al, 2014 since these embryos have shown reduced cryotolerance compared to their in vivo counterparts (tominaga, 2004;mucci et al, 2006;Leme et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have shown increased survival of IVP embryos and higher viability measured at the molecular level (kuwayama et al, 2005;vaJta et al, 2006;stinshoFF et al, 2011;marinho et al, 2015;Leme et al, 2016). However, the efficiency of embryo vitrification remains variable and the influence of several important factors remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, nos últimos 50 anos relata-se queda na taxa de concepção das vacas Holandesas (Marinho et al, 2015). Deste modo, é amplamente aceito que o principal fator envolvido no declínio da fertilidade é o balanço energético negativo pós-parto, devido a priorização de nutrientes, para maximizar a produção de leite (Leroy et al, 2008).…”
Section: Introductionunclassified
“…Para superar este problema, autores relatam que as TEs são efetivamente mais empregadas, pela maior resistência dos embriões, a períodos de estresse térmico, do que os gametas (Chebel et al, 2008). Assim, em áreas tropicais existe crescente interesse no cruzamento entre as raças Bos taurus (Holandês) e Bos indicus (Gir), pela sua maior capacidade de adaptação, produção leiteira e maior eficiência reprodutiva (Marinho et al, 2015). Com base nisso, a produção in vitro de embriões (PIVE) bovinos vem sendo utilizada em escala comercial, por, dentre outras vantagens, permitir um melhor aproveitamento de fêmeas de mérito genético superior e nesse contexto, o Brasil se destaca em escala global, produzindo praticamente a metade de todos os embriões frutos de PIVE de todo o Mundo, e com perspectiva de crescimento (Cristina, 2008).…”
Section: Introductionunclassified
“…W nowszych badaniach podaje się, że sortowanie wpływa na plemniki X i na rozwój blastocyst produkowanych in vitro prawdopodobnie poprzez obniżenie kompetencji rozwojowej wczesnych form rozwojowych zarodków, nie zaś osłabienie zdolności do zapłodnienia (30). Wskaźnik zacieleń nie różnił się w przypadku transferu zarodków uzyskanych z użyciem nasienia sortowanego i konwencjonalnego zarówno w technologii in vitro, jak i in vivo (43,51,67). Wskaźnik ciąży po przeniesieniu zarodków po inseminacji nasieniem sortowanym i niesortowanym w 30. dniu po rui nie różnił się i wynosił, odpowiednio, 57,1% i 57,3%.…”
unclassified